Pressing time Influence on physical and mechanical properties of MDP panels - Lima, Felipe Oliveira [UNESP]; Lirya Silva, Luana Cristal [UNESP]; Campos, Cristiane Inacio de [UNESP]; Christoforo, Andre Luis; Rocco Lahr, Francisco Antonio (Ipef-inst Pesquisas Estudos Florestais, 2018)
Medium density particleboards (MDP) are products that meet the demand of a significant industry sectors. Given the multiple possibilities of applying the MDP, studies that seek to generate subsidies to expand knowledge about the subject are necessary and welcome. In this context, the present work had the objective of producing medium density particulate panels composed of three layers using Eucalyptus ssp. wood residues, varying pressing time (3, 5, 6, 7, 8 and 10 minutes) and evaluating their physical and mechanical properties. The following parameters were determined: density, moisture content, thickness swelling and water absorption, modulus of rupture and elasticity in the static bending, and tensile strength perpendicular to face. Results were submitted to statistical analysis and compared to the requirements of Codes NBR 14810-2 (2013) and EN 312 (2003), as well as the results of other related researches. It is concluded that pressing time does not significantly interfere with panel properties in range of 5 to 10 minutes.
Keywords: Particleboards; Residues; Eucalyptus ssp; Pressing time